2013
DOI: 10.1039/c3dt52178h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and selective de-esterification of diorganotinbis(O-methylphosphite)s

Abstract: A one-pot reaction between di-n-butyl/diethyl/dimethyltin dichloride and dimethylphosphite (MeO)2P(O)H in a solvent free medium (120 °C, 18 h) proceeds smoothly to yield the corresponding diorganotinbis(O-methylphosphite)s, [R2Sn(OP(O)(OMe)H)2]n [R = n-Bu (1), Et (2), Me (3)]. The identity of 1-3 has been established by IR, multinuclear ((1)H, (13)C, (31)P, (119)Sn) NMR, powder X-ray diffraction (PXRD) and X-ray crystallography. The coordination framework in each case adopts a one-dimensional structural motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…15 The structural similarities between the two families are quite apparent in view of the formation of one-dimensional coordination polymers that result from the bridging bidentate bonding mode of phosphonate/phosphite ester ligands. Due to their low-dimensional structural frameworks, both classes of compounds show enhanced solubility in water/organic solvents.…”
Section: Spectral Studiesmentioning
confidence: 98%
“…15 The structural similarities between the two families are quite apparent in view of the formation of one-dimensional coordination polymers that result from the bridging bidentate bonding mode of phosphonate/phosphite ester ligands. Due to their low-dimensional structural frameworks, both classes of compounds show enhanced solubility in water/organic solvents.…”
Section: Spectral Studiesmentioning
confidence: 98%
“…20 Our contribution in this area r e l a t e s t o t h e s y n t h e s i s o f d i o r g a n o t i n b i s (Oalkylorganophosphonate)s, R 2 Sn{O(P)(O)(OR)R} 2 , and their H-phosphonate analogues from the direct reaction between diorganotin dichloride and the corresponding organophosphonic acid dialkyl ester/H-phosphonic acid dialkyl ester. 21,22 The reaction proceeds via the selective cleavage of the (P)O−C bond and the elimination of alkyl halide as the byproduct.…”
mentioning
confidence: 66%
“…Zuckerman et al have reported the synthesis of cyclohexameric triphenyltin O -methylmethylphosphonate, [Ph 3 SnOP­(O)­(OCH 3 )­CH 3 ] 6 , by a series of complex steps involving the Arbuzov rearrangement of a Ph 3 SnOP­(OCH 3 ) 2 intermediate . Our contribution in this area relates to the synthesis of diorganotin bis­( O -alkylorganophosphonate)­s, R 2 Sn­{O­(P)­(O)­(OR)­R} 2 , and their H -phosphonate analogues from the direct reaction between diorganotin dichloride and the corresponding organophosphonic acid dialkyl ester/ H -phosphonic acid dialkyl ester. , The reaction proceeds via the selective cleavage of the (P)­O–C bond and the elimination of alkyl halide as the byproduct.…”
mentioning
confidence: 99%
“…It is important to emphasize that coordination chemistry of these ligands still remains in a state of dormancy despite a few early reports on the synthesis of sila-substituted phosphonic acids . As part of our ongoing interest in metal coordination frameworks derived from oxyphosphorus-based ligands, , we surmised that incorporation of these ligands in the coordination assemblies might offer a possibility to modulate structural motifs as a result of steric and electronic attributes of silaalkyl groups. Herein we report a detailed study on the synthesis and structural aspects of two new silaalkylphosphonic acids, namely, Me 3 SiCR 2 P(O)(OH) 2 [R = H ( 1 ), CH 3 ( 2 )] and diorganotin(IV) coordination polymers Et 2 Sn{OP(O)­(OH)CH 2 SiMe 3 }(OSO 2 Me) ( 3 ), (Et 2 Sn) 6 {O 3 PC­(CH 3 ) 2 SiMe 3 } 4 (OSO 2 Me) 4 ( 4 ), and Et 2 Sn(O 3 P­CH 2 SiMe 3 ) ( 5 ) derived therefrom.…”
Section: Introductionmentioning
confidence: 99%